Pengaruh Variabel Makroekonomi Terhadap Net Interest Margin Industri Perbankan Terdaftar di Bursa Efek Indonesia (BEI) - Berby Berliani (Warta Pendidikan | e-Journal, 2020)
This study aims to determine the effect of external factors, namely the variable Bank Indonesia Interest Rate (SBI), Inflation and Gross Domestic Product (GDP) growth towards the Net Interest Margin (NIM) of Banks listed on the Indonesia Stock Exchange (BEI) in 2013-2017. The research sample consisted of 31 banks taken using purposive sampling technique. The data used is secondary data and is panel data. The analysis technique used is Multiple Linear Regression Analysis with Random Effect model. The results showed that SBI and GDP growth had a positive effect while inflation had a negative effect on the NIM, where only the GDP growth variable had a significant effect on the NIM.